Production and characterization of 166Ho polylactic acid microspheres. (22nd December 2015) - Yavari, Kamal; Yeganeh, Ehsan; Abolghasemi, Hossein
Abstract : Microsphere and particle technology with selective transport of radiation represents a new generation of therapeutics. Poly‐L ‐lactic acid (PLLA) microspheres loaded with holmium‐166 acetylacetonate ( 166 Ho‐PLLA‐MS) are novel microdevices. In this research, 165 HoAcAc‐PLLA microparticles were prepared by the solvent evaporation technique. Microspheres were irradiated at Tehran Research Reactor. The diameter and surface morphologies were characterized by particle sizer and scanning electron microscopy before and after irradiation. The complex stability, radiochemical purity, and in vivo biodistribiotion were checked in the final solution up to 3 days. In this study, 166 Ho‐PLLA spherical particles with a smooth surface and diameter of 20–40 µm were obtained, which were stable in vitro and in vivo studies. Neutron irradiation did not damage the particles. The ease with which the PLLA spheres could be made in the optimal size range for later irradiation and their ability to retain the 166 Ho provided good evidence for their potential use in radioembolization. Abstract : Polylactic acid microspheres have been considered as important drug‐delivery vehicles. In this research, we have synthesized microstructured 166 Ho‐PLLA. Spherical particles with a smooth surface and high labeling yield (99%), radiochemical purity, and excellent in vitro and in vivo stabilities of the prepared complex lead to the conclusion that 166 Ho‐PLLA particles would be useful as a therapeutic agent in the radioembolization.